(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The study was conducted to depict the overall economics of papaya cultivation in four districts namely Tangail, Jashore, Bandarban and Rajshahi. The objectives of the study were to examine the cost structure, resource use productivities, profitability and the problems of papaya production. A total of 152 farmers taking 38 from each district were selected randomly. Data were collected through a pre-tested interview schedule during January-March, 2017. The per hectare use of human labour, plant protection, manures and fertilizer were found to be maximum at Jashore whereas, the per hectare use of saplings was found to be maximum at Tangail district. The per hectare cost of cultivation of papaya was high at Jossere (365405) followed by Tangail (Tk.334261), Rajshahi (Tk.319754), and Bandarban (Tk. 272664). The average per hectare yield were maximum at Jossere (62MT) followed by Rajshahi (55MT), Tangail (54MT) and Bandarban (52MT). Per hectare gross margin was the highest at Tangail (Tk. 802797) followed by Bandarban (Tk. 658441), Jashore (Tk. 536346) and Rajshahi (Tk.471298). Per hectare net return was highest at Tangail (Tk.633738) followed by Bandarban (Tk.507335), Jossere (Tk.346594) and Rajshahi (Tk.302747). The overall benefit cost ratio was 2.39 which indicates papaya cultivation was profitable in Bangladesh. The yield of papaya would increase by 0.0407, 0.125, 00.0627, 0.0863 and 0.3785 % if papaya farmers apply 1% additional human labour, seedlings/saplings, fertilizer, improved variety, and dummy for loamy soil. Attacks on viral disease, adverse weather condition, non-availability of reliable seed, lack of irrigation facilities, lack of technical knowledge and problems in marketing of papaya were the major constraints of papaya cultivation in the study areas. Bangladesh J. Agril. Res. 44(1): 115-126, March 2019